Positioning of Retail Companies: Theoretical Aspects - Ivanauskas, Robertas; Pajuodis, Arvydas (Ekonomika, 2005)
The rapid development of retailing and changes in customers’ shopping behaviour are shifting the competitive situation and stimulate searching for new effective competition strategies. In modern retailing, more and more attention is been paid to positioning, which enables a favourable image in the minds of customers and a differentiation from competitors. The application of the concept of positioning in retailing is quite a new problem. Positioning and the place of image in marketing strategy are briefly discussed in the article. Retail companies’ and retail outlets’ positioning specifics and methodology are analyzed. Special attention is paid to the specifics of multiple retailers’ positioning methodology because of their increasing power within distribution channels and a significant impact on activities of manufacturers and wholesalers and also on customers’ shopping habits. The methods that were used for preparing the article were analysis and summary of scientific literature, modeling and expert evaluation.